The study of drug utilization in pregnancy at outpatient department of Hospital Tengku Ampuan Rahimah; a cross sectional study / Noorazlinda Abdul Rahim - Abdul Rahim, Noorazlinda (2014)
Background: Drug utilisation in pregnant women was not widely studied in clinical studies. Thus it is very important to do a drug utilization review in this population. This study aims to evaluate the drug utilization in pregnancy based on class of drug and based on FDA pregnancy risk category. Methodology: This is a cross-sectional study based on prescription. 9927 prescription was collected from outpatient department of HT AR and was used in gathering the data. Result: The most commonly prescribed drugs other than supplement were antidiabetics 19.8%, followed by antibiotics 14.8% then analgesics and antihistamine 12.3% respectively. Out of 162 patients in total, 33 women (20.4%) received a drug from category A, 97 (60.5%) received the drug from category B, 39 (24.7%) received the drug from category C, 6 (3.7%) received the drug from category D and no patient received the drug from category X. Conclusion: The results of drug use in pregnancy are in line with the rational use of drug since there is no drug category X being prescribed in pregnancy. While drugs category C and D can be used when benefits outweigh potential harmful effects.